2003
DOI: 10.1093/jnen/62.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified NT2N Human Neuronal Cells Mediate Long-Term Gene Expression as CNS Grafts In Vivo and Improve Functional Cognitive Outcome Following Experimental Traumatic Brain Injury

Abstract: Human Ntera-2 (NT2) cells can be differentiated in vitro into well-characterized populations of NT2N neurons that engraft and mature when transplanted into the adult CNS of rodents and humans. They have shown promise as treatments for neurologic disease, trauma, and ischemic stroke. Although these features suggest that NT2N neurons would be an excellent platform for ex vivo gene therapy in the CNS, stable gene expression has been surprisingly difficult to achieve in these cells. In this report we demonstrate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 62 publications
0
55
0
Order By: Relevance
“…Studies have shown the survival of hNT neurons within the CNS of rats after excitotoxin-induced lesions (Hurlbert et al, 1999;Fricker-Gates et al, 2004), middle cerebral artery occlusions (Borlongan et al, 1998a,b,c;Saporta et al, 1999;Willing et al, 2002a), 6-OHDA-induced nigrostriatal lesions (Baker et al, 2000a;Willing et al, 2002b), brain Philips et al, 1999;Watson et al, 2003) and spinal cord injury Christie et al, 2004), as well as in a mouse model of amyotrophic lateral sclerosis Garbuzova-Davis et al, 2002). hNT neurons have also been reported to be safe for transplantation in stroke patients (Kondziolka et al, 2000;Meltzer et al, 2001;Nelson et al, 2002).…”
Section: Hnt Neurons For Cell Replacement Therapy In Pdmentioning
confidence: 99%
“…Studies have shown the survival of hNT neurons within the CNS of rats after excitotoxin-induced lesions (Hurlbert et al, 1999;Fricker-Gates et al, 2004), middle cerebral artery occlusions (Borlongan et al, 1998a,b,c;Saporta et al, 1999;Willing et al, 2002a), 6-OHDA-induced nigrostriatal lesions (Baker et al, 2000a;Willing et al, 2002b), brain Philips et al, 1999;Watson et al, 2003) and spinal cord injury Christie et al, 2004), as well as in a mouse model of amyotrophic lateral sclerosis Garbuzova-Davis et al, 2002). hNT neurons have also been reported to be safe for transplantation in stroke patients (Kondziolka et al, 2000;Meltzer et al, 2001;Nelson et al, 2002).…”
Section: Hnt Neurons For Cell Replacement Therapy In Pdmentioning
confidence: 99%
“…By using specific culture conditions, these NT2-N neurons form functional synapses (Hartley et al, 1999) and express a variety of neurotransmitter phenotypes (Pleasure and Lee, 1993;Yoshioka et al, 1997;Guillemain et al, 2000). This cell line has also been used in several transplantation studies, including engraftments in experimental animals (Ferrari et al, 2000;Watson et al, 2003) and in human patients (Kondziolka et al, 2001).…”
mentioning
confidence: 99%
“…Several key clinical trials have helped shape the field of cell therapy in recent years, for example, the researchers who carried out the Parkinson's disease clinical trials [32][33][34][35][36] providing the foundation for the first cell therapy in stroke patients [37,38]. Their intracerebral transplantation of NT2N cells has provided a model for current clinical trials in chronic stroke patients [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%